Environmental status of Manahara River, Kathmandu, Nepal - Bajracharya, Ramita; Tamrakar, Naresh Kazi (Bulletin of the Department of Geology, 2008)
The Manahara River located in northeast part of the Kathmandu Valley has been disturbed for last one decade by several anthropogenic activities and natural causes thereby deteriorating its recreational functions and stream habitat. To obtain an existing environmental condition and disturbances of the river, the river was surveyed for its habitat, pollution level and surface water quality. Among the five representative segments of the river, the downstream segment (Sano Thimi) was scored into intermediate category showing more pollution and environmental deterioration compared to the upstream segments. Turbidity, electrical conductivity, chemical oxygen demand, biological oxygen demand and ammonia increase, whereas dissolved oxygen decreases from upstream to downstream with exponential functions. Aquatic lives like Garra sp. (Buduna), Schizothorax sp. (Asala), Channa sp. (Hiele) and Heteropneustes sp. (Singe) were observed except in downstream of the Jadibuti Bridge situated downstream from Sano Thimi stretch. Fish species were rare from the Jadibuti area most probably due to reduced dissoved oxygen (5 mg/l). Coliform bacteria ranged from 3000 to 4000 in the Manahara River showing high amount of bacterial contamination. Major disturbances, which affect river habitat and surface water quality of the Manahara River were destruction of riparian buffer zones, excavation excessive amount of sand from the river, encroachment of floodplains and bars, solid waste and sewer effluent, and tendency of landuse change. To retard environmental degradation of the Manahara River from the human-induced activities, local government needs to take immediate action. doi: 10.3126/bdg.v10i0.1417 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 21-32